Pengaruh Green Process, Green Product, Green Image, dan Environmental Cost Terhadap Nilai Perusahaan - Nurul Sulistiyani; Hasnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the influence of Green Process, Green Product, Green Image, and Environmental Cost on Firm Value. This research uses secondary data obtained from annual reports and company sustainability report. The amount of data in this research population is 105 data from manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (BEI) in the period 2021 - 2023. The analysis technique used in this research is multiple linear regression analysis which is processed using SPSS version 30. The results of this research are that Green Process has no effect on Firm Value, Green product has a positive effect on Firm Value, Green Image has no effect on Firm Value, Environmental Cost has no effect on Firm Value.